Back Propagation Neural Network for Wireless Networking - Dahiya, Menal (International Journal of Computer Sciences and Engineering, 2025)
The development in computers and network have changed the world very rapidly in recent years. So, the task of safeguarding the networks is very challenging. Different security algorithms and protocols have been proposed for the proper development of security mechanism. An Artificial Neural Network which is a data processing system consisting of large number of highly interconnected processing elements (neurons) in multiple layers inspired by the structure of human brain that follows a Back Propagation Algorithm can be implemented as a Wireless Network Security system. This paper demonstrates that Neural Network concept is more efficient in the area of Wireless Network Security.